Preliminary investigations on the leaves of Averrhoa bilimbi Linne - Acosta, Rowena Obeda G.
Preliminary tests were performed on the aqueous and alcoholic extracts of the fresh and dried leaves of Averrhoa bilimbi Linne (Fam. Oxilidaceae). Thin layer chromatography and column chromatography were done to separate and isolate the glycosidic constituents established to be present.